Rhythm And Risk: Exploring The Relationship Between Afrobeat Music And Drug Abuse Among Nigerian Universities’ Undergraduate Music Students - Tosin Emmanuel Akinduyo; Patrick Oluwafemi Akerele; N.P.M Mabaso (Indonesian Journal of Learning Education and Counseling, 2024)
Background: Nigeria's music industry attracts young minds, particularly Afrobeat, a popular West African music genre. Nigeria is a hub for Afrobeat with lyrics and videos which significantly influence adolescents' behaviour, emotions, and world perception. Aim: This study aimed to assess and to explore the relationship between Afrobeat music and drug abuse in Nigeria. Setting: A total of 200 music undergraduates’ students and 4 music experts from 6 different universities (University of Jos (North Central); University of Maiduguri, Borno State (North-East); Ahmadu Bello University, Zaria, Kaduna (Northwest); University of Nigeria, Nsukka (South East); University of Benin (South South); and University of Lagos (South West). Methods: The study adopted a mixed method approach, coupling quantitative and qualitative data analysis. The population included 200 music students and five music and lyrics analysts from various universities. The research instrument used was a structured questionnaire, while qualitative data was collected through observation and interview guides. Pilot testing was conducted to ensure the instruments were relevant, unbiased, and appropriate for the study context and participants. Quantitative and thematic analysis was conducted. Results: Results indicate that Afrobeat music in Nigeria may promote drug abuse, with 77% of lyrics, videos, and lifestyles featuring drug-related content. This can influence youth attitudes and behaviors towards drugs. The mediating influence of ethnic identity and substance use among young adults is also examined, with the glamorization of drug use potentially promoting or discouraging substance abuse. Conclusion: Despite the efforts of previous researchers, this study observes a gap in the area of guidelines for airing offensive, vulgar, or inappropriate content, including explicit lyrics, violence promotion, or harmful societal content (such as glamourizing and normalizing drug use and abuse).